The Students’ Perception and Satisfaction in the Kampus Mengajar Program at Seventh Semester of Universitas Pendidikan Muhammadiyah Sorong - Martha Rosina Gefilem; Rizqi Claudia Wardani.H; Raisa Anakotta (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
This study examines students’ perceptions and satisfaction toward the Kampus Mengajar program among seventh-semester students at Universitas Pendidikan Muhammadiyah Sorong. The program, part of the Merdeka Belajar Kampus Merdeka (MBKM) initiative, aims to provide students with teaching experience and opportunities for professional growth beyond the classroom. Employing a mixed-method approach, the study combined quantitative and qualitative data. Eight students from different study programs participated, representing those who had joined Kampus Mengajar. Data were collected through a questionnaire consisting of 25 close-ended items to measure satisfaction and an interview with seven open-ended questions to explore perceptions. The findings indicate that students generally perceive Kampus Mengajar as a valuable and meaningful program. They reported gaining teaching experience, improving communication and classroom management skills, developing self-confidence, and expanding professional networks. Despite these benefits, some students noted challenges such as delayed stipends, school placements that did not match their study fields, and limited credit conversions. Quantitative data revealed an average satisfaction rate of 76.3%, categorized as high satisfaction. Overall, Kampus Mengajar is considered an effective program that enhances students’ academic and professional readiness, though improvements in administrative and placement systems are still needed.